Would it be recommended treating multiple sclerosis relapses with high dose oral instead intravenous steroids during the COVID-19 pandemic? Yes (2020)
The emergence of novel Coronavirus 2019 and the subsequent pandemic are presenting a challenge to neurologists managing patients with multiple sclerosis (MS). The clinical management has dramatically altered and it was necessary to change and/or adapt it to the new situation. Regarding relapses management, the use of intravenous corticosteroids and hospitalization during MS relapses increase the risk of viral exposure. Objective: To review the efficacy and safety of high dose oral corticosteroids in acute relapses treatment compared to intravenous corticosteroids. Methods: Descriptive review of the utility of high dose oral corticosteroids for MS relapses treatment was performed. We searched the literature available on PubMed and Scientific Electronic Library Online (Scielo). We focused on different trials comparing the use of high dose intravenous vs oral corticosteroids. Results: Five studies were selected. One hundred and eighty two patients receiving treatment with high dose oral corticosteroids were included. The most frequent schedule was oral methylprednisolone 1000 mg (over three days). There were no significant differences between both routes of corticosteroids administration. Conclusion: Neurologists should be aware of the current evidence on the similar efficacy of both oral and intravenous corticosteroids for MS relapses. Using oral steroids during the pandemic would be a safe option for patients.